First Detection and Genetic Characterization of Felis catus Papillomavirus Type 11, the First Treisetapapillomavirus Type to Infect Domestic Cats - John S. Munday; Adrienne F. French; Louisa Broughton; Xiaoxiao Lin; Sarah D. Bond; Simona Kraberger; Matthew A. Knox (Animals)
Domestic cats are currently recognized to be infected by 10 different Felis catus papillomavirus (FcaPV) types that are classified into three genera. Examination of a skin sample from a cat with presumptive allergic dermatitis revealed clusters of large amphophilic intracytoplasmic bodies within epidermal cells. A 312 bp section of DNA from a novel PV type was amplified from the sample, while the entire 7569 bp genome was amplified and sequenced from a skin swab. The novel PV, which was designated FcaPV11, was predicted to contain coding regions for five early proteins and two late ones. Phylogenetic analysis of the L1 gene sequence showed FcaPV11 clusters with members of the Treisetapapillomavirus genus and shares less than 64% similarity with any of the previously fully sequenced FcaPV types. FcaPV11 DNA was not detected in a series of neoplastic and non-neoplastic skin samples from an additional 30 cats. These results show, for the first time, that cats can be infected by members of the Treisetapapillomavirus genus and suggest PVs in this genus may have co-evolved with a common Carnivora ancestor. While FcaPV11 was considered unlikely to have caused skin lesions in this cat, the prominent PV-induced cell changes indicate the PV can influence cell regulation. This suggests FcaPV11 may have the potential to cause skin disease in cats.